Editorial board publication strategy and acceptance rates in Turkish national journals - Tutuncu Lokman (Journal of Data and Information Science, 2023)
This study takes advantage of newly released journal metrics to investigate whether local journals with more qualified boards have lower acceptance rates, based on data from 219 Turkish national journals and 2,367 editorial board members.